Kelayakan Media Pembelajaran Prezi Menggunakan Pendekatan Saintifik - Ningsih, Diyah Ayu Setia; Komikesari, Happy (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This research aims to know the feasibility of prezi-based learning media using scientific approach on the material of SMP / MTs caloric level. This research uses research and development method by using model from Borg and Gall which is adapted from Sugiono development model. The data of this study were obtained from questionnaire responses of educators and learners, questionnaire validation of material experts and media experts. The type of data produced is qualitative data which is analyzed by guidance criteria of assessment category to determine product quality. Researchers produce a product in the form of prezi-based learning media using scientific approach on the material of SMP / MTs caloric level. Based on the assessment of material experts get the percentage of 84.13% with very decent category, the assessment of media experts get the percentage of 84.62% with very decent category while the response of the students of the three schools received an average percentage of 84.8% in very decent category . Based on the assessment by material experts, media experts, educators and students' responses, it can be concluded that prezi-based learning media using scientific approach on caloric materials of junior high school / MTs is suitable for learning media. Abstrak: Penelitian ini bertujuan untuk; Mengetahui kelayakan media pembelajaran  berbasis prezimenggunakan pendekatan saintifik pada materi kalor tingkat SMP/MTs. Penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development) dengan menggunakan model dari Borg and Gall yang diadaptasi dari model pengembangan Sugiono. Data penelitian ini diperoleh dari angket respon pendidik dan peserta didik, angket validasi ahli materi dan ahli media. Jenis data yang dihasilkan adalah data kualitatif  yang dianalisis dengan  pedoman kriteria kategori penilaian untuk menentukan kualitas produk. Peneliti menghasilkan suatu produk berupa media pembelajaran berbasis prezi menggunakan pendekatan saintifik pada materi kalor tingkat SMP/MTs. Berdasarkan penilaian ahli materi mendapatkan persentase 84,13% dengan kategori sangat layak, penilaian ahli media mendapatkan persentase 84,62% dengan kategori sangat layaksedangkan  respon peserta didik ketiga sekolah tersebut memperoleh nilai presentase rata-rata sebesar 84,8 % dalam kategori sangat layak. Berdasarkan penilaian oleh  ahli materi, ahli media, pendidik dan respon peserta didik maka dapat disimpulkan bahwa media pembelajaran berbasis prezi menggunakan pendekatan saintifik pada materi kalor tingkatSMP/MTs layak digunakan sebagai media pembelajaran